Cardiovascular Screening Rates With Establishment of Postpartum Cardiovascular Care Pathway for Hypertensive Disorders of Pregnancy - Madelyn Hurwitz, BA; Asma Rayani, MBBS, ScM; Jared A. Spitz, MD; Andrew H. Nguyen, DO; Ain Shajihan, MD; Olayinka J. Agboola, MD, MPH; Sharmaine McCoy, DNP, NP; Lily N. Dastmalchi, DO; Antonio F. Saad, MD, MBA; Scott A. Sullivan, MD; Yaa Adoma Kwapong, MD, MPH; Roxanne Mirabal-Beltran, PhD, RN; et al. (JACC: Advances)
Background: Hypertensive disorders of pregnancy (HDP) are associated with an increased risk of cardiovascular disease, highlighting the importance of thorough cardiovascular screening in individuals with prior HDP. Objectives: This retrospective cohort study evaluated rates of cardiovascular screening studies (lipid panel, lipoprotein(a), apolipoprotein B, hemoglobin A1c) ordered by cardiology in the first year postpartum before and after establishment of a postpartum cardiovascular care pathway within the Inova Health System. Methods: The study population included postpartum adults with recent pregnancies complicated by HDP seen by designated clinicians after care pathway establishment (7/1/23-3/31/24) in the cardio-obstetrics cohort (n = 113) or by cardiology before care pathway establishment (6/1/20-6/30/23) in the historical cohort (n = 179). Sociodemographic and clinical characteristics and rates of screening ordered were evaluated between cohorts. Results: There were no significant differences between cohorts in age, race/ethnicity, parity, prior history of HDP, or rates of pre-eclampsia. The mean age across both cohorts was 33 years. The cardio-obstetrics cohort had significantly higher rates of screening ordered compared to the historical cohort: lipid panel: 85.0% vs 33.0%, lipoprotein(a): 62.8% vs 6.2%, apolipoprotein B: 31.0% vs 1.1%, and hemoglobin A1c: 76.1% vs 18.4% (all P < 0.001). Evaluation of prepregnancy and postpregnancy cardiometabolic health parameters and electronic medical record-based social determinants of health and psychological health screening demonstrated elevated rates of risk factors across both cohorts. Conclusions: Implementation of a postpartum cardiovascular care pathway is feasible and is associated with significantly increased rates of cardiometabolic risk factor screening ordered in the first year postpartum.